2010
DOI: 10.1111/j.1600-0668.2009.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing exhaled airflow from breathing and talking

Abstract: Practical ImplicationsAccurate prediction of airborne disease transmission, and the infection prone zones, can aid in identifying and implementing the control strategies. With the recent advancements, Computational Fluid Dynamics (CFD) has become a powerful tool in predicting the disease transmission. Accurate prediction of the transmission by these CFD simulations requires information on sources and sinks of infectious viruses and models for dispersion of these viruses. The exhaled air of an infected human is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
405
5
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 474 publications
(433 citation statements)
references
References 25 publications
17
405
5
6
Order By: Relevance
“…A more detailed overview on the structure of the cough generator can be found in our latest study (Liu and Novoselac, 2014). The cough generator produces a square-wave manner cough that is different from cough's released from the human body and in previous studies (Zhu et al, 2006;Gupta et al, 2009). During measurement period, a stable particle concentration in the cough jet was achieved.…”
Section: Generation Of Particle-laden Cough Jetmentioning
confidence: 99%
See 3 more Smart Citations
“…A more detailed overview on the structure of the cough generator can be found in our latest study (Liu and Novoselac, 2014). The cough generator produces a square-wave manner cough that is different from cough's released from the human body and in previous studies (Zhu et al, 2006;Gupta et al, 2009). During measurement period, a stable particle concentration in the cough jet was achieved.…”
Section: Generation Of Particle-laden Cough Jetmentioning
confidence: 99%
“…The airtemperature was kept as 32.0 ± 0.5°C inside the cough generator by using a 12-voltage 20-watt tungsten halogen bulb. The total cough volume may have a variation of 0.8-5.0 L cough -1 (Zhu et al, 2006; Gupta et al, 2009). In this study, the total cough air volume was set as 1.4 L cough -1 with a maximum cough velocity of 6.0 m s -1 over a period of 1 second.…”
Section: Generation Of Particle-laden Cough Jetmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these body activities, normal respiration also poses great potential for energy harvesting. Detailed studies on human breathing showed that watt-level power is available in the form of fluid flow [8][9][10], which indicates that milliwatts can be generated with a harvester having a few percent efficiency.…”
Section: Introductionmentioning
confidence: 99%